2008
DOI: 10.1016/j.chemphys.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The electronic states of thiazole studied by VUV absorption spectroscopy and ab initio configuration interaction methods

Abstract: The thiazole VUV absorption spectrum over the range 5-12 eV shows intense bands near 5.4, 6.0, 7-7.8, 8.2-8.8, 9.2-10.1 and 10.2-11.0 eV; there is marked vibrational structure in the 7.5-8.5 and 10.2-11 eV regions. A number of Rydberg states have been identified, largely from IE 1 , but also tentative values for ones from IE 2 and IE 4 . Electronic excitation energies for valence and Rydberg-type states have been computed using ab initio multi-reference multi-root CI methods, and these have been compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Therefore, the present study is an attempt to see how these observed variations in the target properties affect the electron impact scattering crosssectional data. Comparing our present results with the available data, it is observed that the calculated ground state energies align closely with the existing data [24][25][26][27]. Additionally, our calculated dipole moment demonstrates excellent agreement with the available experimental data [28] in comparison to those value reported by Kossoski & Bettega [23], notably in the case of isoxazole.…”
Section: Ionization Cross-sectionsupporting
confidence: 91%
“…Therefore, the present study is an attempt to see how these observed variations in the target properties affect the electron impact scattering crosssectional data. Comparing our present results with the available data, it is observed that the calculated ground state energies align closely with the existing data [24][25][26][27]. Additionally, our calculated dipole moment demonstrates excellent agreement with the available experimental data [28] in comparison to those value reported by Kossoski & Bettega [23], notably in the case of isoxazole.…”
Section: Ionization Cross-sectionsupporting
confidence: 91%
“…The highest occupied valence molecular orbitals of thiazole in the VUV, calculated at MP2(full)/aug‐cc‐pVTZ level, have the following energies (eV) and symmetries: 9.35 (A″), 10.75 (A″), 11.87 (A′), 13.89 (A′), 15.42 (A″), 15.58 (A′), 16.33 (A′), 19.10 (A′), 21.22 (A′). The order for the main valence orbitals and Rydberg states of thiazole molecule has been previously discussed by Palmer . Considering the Cs symmetry of this molecule, no complete separation of the valence and Rydberg orbitals may be observed, thus some mixing of the valence molecular orbitals is expected.…”
Section: Resultsmentioning
confidence: 73%
“…Despite the relevance of spectroscopic investigations concerning the electronic structure, photoionization and dissociation dynamics, as well as the study of resulting ionic fragments and radical species from the free thiazole molecule, only a limited number of reports have been found in the literature. Briefly, the valence absorption and photoelectron spectra of thiazole molecule have been reported by Daamen et al ., and Palmer . The latter reported the vertical ionizations energies in the VUV range and the assignments based on ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Very few theoretical and experimental studies for thiazole dedicated to the valence electronic levels can be found in the literature . On the other hand, we noticed a lack of information concerning the processes of electronic excitation and relaxation dynamics, photoionization, and photodissociation, involving the core electron levels for this molecule.…”
Section: Discussion and Resultsmentioning
confidence: 86%